Avaliação de força de preensão manual e teste de usabilidade em embalagens com tampas de segurança: parâmetros para o design ergonômico - Bonfim, Gabriel Henrique Cruz [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
It is very important that the ergonomic aspects such as safety, comfort and well-being be considered in manipulating objects to contemplate the physical and mental skills of the users as well as various characteristics, such as gender and age. Packages are examples of common manual interfaces of everyday life, among those examples are the Child Resistant packaging (CRP) that require more of one movement to be opened, which leads the user to serious difficulties in opening, causing embarrassment especially in those people with lower biomechanical capabilities, such as women or the elderly. Therefore, the packaging design should be aware of the ergonomic requirements in order to develop products that are reliable and secure. In the case of CRP, they must be bath accessible to elderly and inaccessible to children. In Brazil, such packages are nat mandatory, but they can be found in several products, such as mauthwashes with a squeeze-and-turn cap system. However, many studies have shown that those packages are considered difficult to open, especially to the elderly. Therefore, this study aimed to evaluate and analyze the influence of the design in usability and the application of manual forces during an opening simulation of mouthwashes with squeeze-and-turn caps. So, a usability test, with 67 subjects of different genders and age group, was performed using three packages of mouthwashes with different shapes. A biomechanical evaluation (grip torque) was also performed in a simulated task with 113 individuals of different genders and age group, using the same packages. The results showed that the package with the largest cap affers the best of usability and force application, mainly due to the design of the cap, because its size allows better visualization of the opening instructions, that cap also has grooves only at the places where it should be pressed, which provides greater friction between cap and fingers, enabling a higher application...

É muito importante que os aspectos ergonômicos como segurança, conforto e bem estar sejam considerados na manipulação de objetos para que contemplem as capacidades física e mental dos usuários, bem como características variadas, como gênero e idade. As embalagens são exemplo de interfaces manuais comuns do cotidiano, dentro desse exemplo encontram-se as Embalagens Especiais de Proteção à Criança (EEPCs) que necessitam de mais de um movimento para serem abertas, o que pode levar o usuário a ter sérias dificuldades na tentativa de abertura, gerando constrangimentos principalmente naqueles com menores capacidade biomecânicas, como as mulheres ou os idosos. Por isso, o design de embalagens deve estar atento aos requisitos ergonômicos a fim de disponibilizar produtos que sejam confiáveis e seguros. No caso das EEPCs, elas devem ser ao mesmo tempo acessíveis a idosos e de difícil acesso para crianças. No Brasil, tais embalagens não são obrigatórias, mas podem ser encontradas em diversos produtos, como por exemplo os enxaguantes bucais que se utilizam de uma tampa com sistema de abertura do tipo aperte e gire (squeeze and turn). Entretanto, muitos estudos mostram que essas embalagens difíceis de abrir, especialmente por parte dos idosos. Por esse motivo, esse estudo objetivou avaliar e analisar a influência do design na usabilidade e na aplicação de forças manuais durante uma simulação de abertura de enxaguantes bucais com tampas de proteção. Para isso foi realizado um teste de usabilidade com 67 sujeitos de diferentes gêneros e faixas etárias, utilizando três embalagens de enxaguantes bucais com diferentes formatos. Também foi realizada uma avaliação biomecânica (preensão de torque), em atividades simuladas com 113 indivíduos de diferentes gêneros e faixas etárias, utilizando as mesmas embalagens. Os resultados mostram que a embalagem com maior tampa oferece as melhroes condições de usabilidade e...
Keywords: Design centrado no usuário; Ergonomia; Desenho industrial; Embalagens; Crianças; User-centered system design